Treadmill in Parkinson’s: influence on gait, balance, BDNF and Reduced Glutathione - Luciana Dias Belchior; Betina Santos Tomaz; Ana Paula Vasconcellos Abdon; Norberto Anizio Ferreira Frota; Daniela Gardano Bucharles Mont’Alverne; Danielle Macêdo Gaspar (Fisioterapia em Movimento)
Abstract Introduction: Parkinson’s disease (PD) is characterized by nigrostriatal degeneration, with dopaminergic depletion, and inflammatory and oxidative changes in the brain, leading to movement and coordination disorders. Recent studies have shown that treadmill training can be beneficial for these patients, but there is little evidence assessing the related blood parameters, such as oxidative stress and neurotrophin levels. Objective: Assess the influence of treadmill training for patients with Parkinson’s on gait, balance, Brain-Derived Neurotrophic Factor (BDNF) and reduced glutathione. Methods: Twenty-two patients with PD (Hoehn and Yahr II and III), older than 40 years, were randomly allocated to two groups: CG (n = 12) - drug treatment and IG (n = 10) - treadmill. Assessments related to functional capacity (quality of life, static and dynamic analysis of gait) and blood parameters such as GSH and BDNF were conducted before and after the eight-week intervention. Results: The demographic data of the groups were homogeneous in terms of age, sex, height, weight, time since disease onset, mini mental examination and the geriatric depression scale. Significant intergroup differences were found for the mental component summary, surface variation, latero-lateral oscillation, antero-posterior oscillation and mean velocity in the post-intervention period. The IG exhibited a strong association between BDNF and GSH, with statistically significant values. Conclusion: It was concluded that controlled treadmill walking improves static balance, quality of life and plasma BDNF and GSH levels in patients with PD.